Effects of supplementation strategies for beef cattle in tropical grassland conditions (Research, Society and Development, 2020)
This study was realized to evaluate the dry matter intake, nutrient digestibilities, and animal performance of crossbred steers grazing Brachiaria brizantha cv. Marandu, during the rainy season. Thirty-three crossbred steers with an average weight of 203.5 ± 39.5 kg were distributed in a completely randomized design with three treatments and eleven replications. The results were analyzed using an ANOVA and a Tukey test with a 5% probability of error. The three experimental diets were: MSA – mineral salt ad libitum; MSU - mineral salt + urea ad libitum and PSU - protein supplementation (0.1% of body weight). The dry matter intake of forage and total dry matter intake were similar (P > 0.05) among treatments. The dry matter, organic matter, neutral detergent fiber, crude protein, ether extract, non-fibrous carbohydrates and total carbohydrates digestibilitities coefficients were influenced (P < 0.05) by treatments. The final body weight, average daily gain, and feed efficiency were similar (P > 0.05) among treatments. The supplementation strategies used during the rainy season resulted in a similar performance; therefore, the strategy adopted could be chosen according to the economical and regional conditions of the production.